Kriptografi dan Skema Keamanan pada Jaringan Sensor Nirkawat - Taufiq Wirahman (Pusat Penelitian Informatika - LIPI, 2012)
This paper attempts to explore the security issues in sensor network that include constraints in sensor networks security, the requirements of secure sensor networks, attack classification and its counter measures and security mechanisms at wirelesssensor network (WSN) such as cryptography and key management. Popularity of wireless sensor network is increasing because of its potential to provide low-cost solution for a variety of real-world problem. As a special form of ad-hoc networks, sensor networks has many limitations that lead to vulnerabilities in security issues. Currently, there are many researches in the field of sensor network security. Our analysis shows that symmetric key cryptography systems are more favorable to provide WSN security services because of its computation and energy cost. Moreover, distributed combine with pre-distributed key management is important to overcome security threats and centralize threats detection is more favorable to reduce energy and computation cost of sensor nodes.